DEVELOPMENT OF BIOLOGY E-MODULES USING PROFESSIONAL PDF FLIP APPLICATIONS ON HUMAN RESPIRATORY SYSTEM MATERIALS - Natalia Kristiani Lase; Krisdayani Harefa (Sean Institute, 2022)
This research is based on the observations of researchers at SMA Negeri Gunungsitoli Idanoi. In learning activities, students still have difficulty understanding the subject matter and have never used print modules or electronic modules in biology learning. The aims of this study were (1) to determine the development of e-modules using Flip PDF Professional on the respiratory system material in humans in class XI of SMA Negeri 1 Gunungsitoli Idanoi with an R&D development model. (2) Knowing the feasibility of e-modules using the Flip PDF Professional application on respiratory system materials in humans in class XI SMA Negeri 1 Gunungsitoli Idanoi, by experts/validators and subject teachers. (3) Knowing the practicality of e-modules using the Flip PDF Professional application on respiratory system materials in humans in class XI of SMA Negeri 1 Gunungsitoli Idanoi. (4) Knowing the effectiveness of e-modules using the Flip PDF Professional application on respiratory system materials in humans in class XI of SMA Negeri 1 Gunungsitoli Idanoi. This research is a type of development research with an R&D model. Data were collected using a validation questionnaire, student response questionnaires, and learning outcomes tests. The research was conducted at SMA Negeri 1 Gunungsitoli Idanoi in class XI MIPA-1 and XI MIPA-2. Based on the results of the research, the results of the feasibility by the material validator reached 98%, the feasibility of the language 97.5%, and the feasibility of the design 97.2%, meaning that the e-module is very feasible to be tested. The practicality of the e-module in the small group trial was 89.2% in the practical category, in the field trial it reached 100%, the very practical category. The effectiveness of the e-module in the product trial class reached 71% in the effective category, and in the use trial, 91.3% in the very effective category.